Methodological Mismatch: Diversity in Sanskrit PhD Dissertations - Bhandari, Krishna Prasad; Bhattarai, Bhawani Shankar; Timilsina , Mahananda (Haimaprabha, 2026)
This research explores methodological and structural deviations in selected Sanskrit PhD dissertations. Despite the long and incessant rational and academic history of Sanskrit, formal doctoral research in Sanskrit studies is a relatively recent practical phenomenon. Since the institutionalization of Sanskrit PhD programs in India and Nepal, noteworthy variations have emerged in the structural organization, methodological orientation, and stylistic conventions of dissertations. This article examines the nature and extent of such variations by analyzing selected Sanskrit PhD dissertations submitted to universities in India, Nepal, and selected Western institutions. For this the study applies the genre analysis theory of John Swales Vijay Bhatia. The study identifies a profound mismatch between prescribed research methodologies—both traditional Sanskrit research conventions and modern Western academic styles—and their genuine application in doctoral theses. The findings divulge considerable inconsistencies not only across universities but also within the same faculty, discipline, and academic session. This methodological disharmony has generated confusion among emerging researchers and emphasizes the urgent need for a standardized yet discipline-sensitive research framework for Sanskrit doctoral studies.